Early Drug Development and Evaluation of Putative Antitubercular Compounds in the -Omics Era - Minias, Alina; Żukowska, Lidia; Lechowicz, Ewelina; Gąsior, Filip; Knast, Agnieszka; Podlewska, Sabina; Zygała, Daria; Dziadek, Jarosław (Frontiers in Microbiology, 2021)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. According to the World Health Organization, the disease is one of the top ten causes of death of people worldwide. M. tuberculosis is an intracellular pathogen with an unusually thick, waxy cell wall and a complex life cycle. These factors, combined with M. tuberculosis ability to enter prolonged periods of latency, make the bacterium very difficult to eradicate. The standard treatment of tuberculosis requires 6 to 20 months, depending on the drug susceptibility of the infecting strain. The need to take cocktails of antibiotics to treat tuberculosis effectively and the emergence of drug-resistant strains prompts the need to search for new antitubercular compounds. This review provides a perspective on how modern -omic technologies facilitate the drug discovery process for tuberculosis treatment. We discuss how methods of DNA and RNA sequencing, proteomics, and genetic manipulation of organisms increase our understanding of mechanisms of action of antibiotics and allow the evaluation of drugs. We explore the utility of mathematical modeling and modern computational analysis for the drug discovery process. Finally, we summarize how -omic technologies contribute to our understanding of the emergence of drug resistance.